The Correlation Between Assessment for Learning and Constructive Alignment Based on Age - Akib, Erwin; Martuty, Arie; Ghaffar, Mohd. Najib bin Abdul; Ahmad, Jamilah binti (Faculty of Education Universitas Negeri Malang, 2019)
he assessment practice in Indonesian Higher Education presently uses the traditional methods, which are assessment for learning and assessment as learning. However, the new perspective on assessment proposes that it should include the process of learning called Assessment for Learning (AFL) and this assessment can be enhanced through the Constructive Alignment (CA) method. The main objective of this study was to determine the correlation between AFL and CA based on age. The respondents of this study were 454 lecturers of 11 Universities selected through multistage cluster sampling method. This study used explanatory sequential design, a combination of quantitative and qualitative method. Quantitative data were obtained using questionnaires followed by qualitative data collection using interviews. The qualitative data were used to explain the quantitative data results. Quantitative data were analyzed using ANOVA, chi-square, and SEM. The validity and reliability of the instruments were determined using the Rasch Model. The findings showed that there was a high correlation level of AFL and CA practice among the lecturers.Keywords: Assessment for Learning, Constructive Alignment, Indonesian Higher Education